Penurunan Derajat Kesehatan Pedagang Akibat Pajanan Debu PM10 di Kawasan Pasar Siteba Kota Padang - Aria Gusti; Ayu Arlesia; Luthfil Hadi Anshari (Faculty of Public Health, Hasanuddin University, Makassar, 2018)
PM10 is a harmful dust that can cause various health problems, especially increased respiratory diseases.This study aims to determine the level of environmental health risk through the analysis of risk of PM10 exposureto traders in Siteba market area and risk management can be done. This research uses Environmental Health RiskAssessment (EHRA) method. The study was conducted from November 2016 to March 2017, with 45 respondents.The sampling technique is accidental sampling. Data analysis is univariate and EHRA. The average concentrationof PM in the three sampling sites was 150 μm/Nm3. The reference concentration value (RfC) of PM10 is 0.014mg/kg/day. The lifetime value of PM10 through inhalation at Kodam Intersection and Perumnas Intersection hasa value of RQ>1, indicating that the exposure is not safe for traders so it is necessary to control and based onPM10 exposure of realtime intake through inhalation in the three sampling sites indicates that exposure is safe ornot there is a risk to the trader with a RQ value <1. The results of the lifetime risk show that two sampling sitesof Kodam Intersection and Perumnas Intersection have risks with RQ>1, which shows that traders are at risk ofdeveloping respiratory problems in the next 30 years.